Economic Analysis of Primary Eye Care Services Provided through Vision Centers in Eastern India. (2nd November 2019) - Kumar SG, Prem; Banerjee, Sandip; Pal, Sushami; Kundu, Sabitra; Mishra, Sukanta; Kurian, Elizabeth
ABSTRACT: Purpose : Primary eye care services delivered through vision centres (VC) form an essential part of the national blindness control efforts, but systematic data on the outputs and cost of providing such services in India are not readily available for further planning and efficient use of resources. Methods : Detailed cost and output data were collected from written records for 2017–2018 fiscal year using standardized methods at nine VC in Kolkata city in West Bengal, India. The total economic cost for these VC was computed and the relation of unit cost of services per patient screened with VC scale was assessed using regression analysis. Break-even point was estimated from average and marginal cost functions. Results : 25, 009 patients were screened at the 9 VC (range 709–5, 717; median 2, 826). The overall total economic cost was INR 7, 304, 172 (USD 113, 306), ranging from INR. 509, 618 (USD. 7, 905) to INR. 1, 390, 855 (USD. 21, 576). Personnel salaries made up 37.8% of the total cost. The unit economic cost of screening a patient was INR 292.1 (USD 4.4) and varied threefold between 9 VC. With a multiple regression model ( p < .035, R 2 = 0.797), apart from the fixed costs, the incremental cost for each patient screened was INR 81.33 (USD 1.26). Break-even analysis suggested that 44.4% of the VCs were functioning below optimal scale. Conclusion : A further reduction in the unit costs is possible if the optimal scale of services is achieved. These findings can inform resource requirement for the primary eye care services in India.